Propriedade, cidade e proteção jurídico-urbanística do patrimônio cultural: estudo de caso sobre o tombamento do edifício São Pedro na cidade de Fortaleza - Monteiro, Vladia Marques (2021)
The present work aims to analyze the case of the legal-urban protection of the São Pedro Building, which is a building located in the city of Fortaleza-CE and considered local cultural heritage. The building is currently in a state of disrepair, suffers from uncommitted duties to conservation, has a requalification project whose legal adequacy is intended to be investigated, in addition to representing a building with importance for the collective memory of the city. For the fulfillment of this intention, the first chapter addresses one of the most striking legal categories for the present case, which is the right to property, more precisely the right to property to be exercised in an urban environment and its respective obligations towards sociability. It also understands the intelligibility that comes from the Superior Court of Justice (STJ) for similar cases, especially with regard to the duty to preserve properties of cultural relevance. The second chapter, in turn, brings an interdisciplinary approach to the right to the city, the process of fixing and creating urban centers in Brazil, its dialogue with globalization processes, in addition to the investigation that focuses on the protection of urban life, since the national, state and municipal panorama, including the destruction of instruments aimed at cooling real estate speculation in the city of Fortaleza, as was the case with the progressive IPTU over time. For the two initial chapters, the qualitative method and the bibliographic review technique were used. Finally, in the third and last chapter, the specifics of the case itself were analyzed. Research techniques were applied, such as interviews with social, academic and institutional voices about the building's tipping, structured questionnaires applied to a sampling of fortress passersby around the building and documentary analysis of the administrative and judicial processes related to the case. The third chapter seeks to answer questions about the relevance to the community of the existence of a cultural asset, if there was inoperation of the Public Power in the course of the administrative declaration of cultural importance, what values are attacked in the case of the São Pedro Building and if there is a supedaneous urban legislation for the requalification required by the owners